Soft canons : American women writers and masculine tradition - Kilcup, Karen L. (University of Iowa Press, 1999)
"In their innovative treatments of seemingly incomparable works, these critics promote dialogue not only about the texts under consideration but also about the very nature of how we read across lines of gender, race, class, and history. Individually, the essays are insightful and strong; collectively, they highlight the vibrancy of current research on nineteenth -century American women writers in particular and nineteenth-century American literature in general ... an ideal critical companion for upper-level undergraduate or graduate courses."--Annie Merrill Ingram, Symploke